2016
DOI: 10.1016/j.bjm.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Soil bacteria showing a potential of chlorpyrifos degradation and plant growth enhancement

Abstract: BackgroundSince 1960s, the organophosphate pesticide chlorpyrifos has been widely used for the purpose of pest control. However, given its persistence and toxicity towards life forms, the elimination of chlorpyrifos from contaminated sites has become an urgent issue. For this process bioremediation is the method of choice.ResultsTwo bacterial strains, JCp4 and FCp1, exhibiting chlorpyrifos-degradation potential were isolated from pesticide contaminated agricultural fields. These isolates were able to degrade 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(70 citation statements)
references
References 34 publications
(42 reference statements)
2
66
0
2
Order By: Relevance
“…resinovorans (12), Ps. fluorescens (13), Bacillus subtilis (13,14,15,16), Bacillus sp and Micrococcus sp (17,18), B. firmis (19), B. cereus (20), Stenotrophomonas (21), Serratia marcescens, Klebsiella oxytoca (22), Achromobacter sp, Ochrobactrum sp (23), Alcaligenes faecalis (24), Mesorhizobium (25), cellulomonas fimi (26), Gordonia (27), B. polymyxa (28), Kocuria sp (29), Staphylococcus sp, Streptococcus sp, azomonas sp, Flavobacterium sp (30) were extensively studied in degradation of chlorpyrifos.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
See 1 more Smart Citation
“…resinovorans (12), Ps. fluorescens (13), Bacillus subtilis (13,14,15,16), Bacillus sp and Micrococcus sp (17,18), B. firmis (19), B. cereus (20), Stenotrophomonas (21), Serratia marcescens, Klebsiella oxytoca (22), Achromobacter sp, Ochrobactrum sp (23), Alcaligenes faecalis (24), Mesorhizobium (25), cellulomonas fimi (26), Gordonia (27), B. polymyxa (28), Kocuria sp (29), Staphylococcus sp, Streptococcus sp, azomonas sp, Flavobacterium sp (30) were extensively studied in degradation of chlorpyrifos.…”
Section: Issn: 2320-5407mentioning
confidence: 99%
“…Growth response of the isolates and degradation were observed at every 48-72 hrs interval in spectrophotometer at 600 nm (23). The content of the flasks were checked by taking 5 ml of culture drawn from mineral based medium and centrifuged at 5000 rpm for 10 minutes.…”
Section: Degradation Of Chlorpyrifos:-mentioning
confidence: 99%
“…strain C1, probably requiring only few days more to achieve complete CHL elimination. A study reported that A. xylosoxidans JCp4 was able to mineralize 100 mg L −1 CHL completely after ten days with only a transient accumulation of TCP [40]. Our work constitutes one of the few reports of Achromobacter as CHL-degraders.…”
Section: Discussionmentioning
confidence: 64%
“…Biodegradation of chlorpyrifos and the bacteria involved in this process are well studied [2,14,31]. However, biodegradation of chlorpyrifos in relation to the metabolic nature of bacterial community is not explored.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorpyrifos and other insecticides (carbofuran, thiomethoxam, imidacloprid) inhibit phosphate solubilising bacteria [28]. Chlorpyrifos also inhibits beneficial plant growth promoting microorganisms in soil [2]. In natural ecosystem chlorpyrifos is degraded to diethylthiophosphoric acid (DETP) and 3,5,6-trichloro-2-pyridinol (TCP) [25].…”
Section: Introductionmentioning
confidence: 99%